Neuroglial Roots of Neurodegenerative Diseases: Therapeutic Potential of Palmitoylethanolamide in Models of Alzheimer's Disease - Scuderi, Caterina; Steardo, Luca (CNS & Neurological Disorders - Drug Targets, 2013)
The growth of knowledge about the molecular mechanisms underlying Alzheimer's disease (AD) has highlighted the role of neuroinflammation in the pathophysiology of this disorder. AD is classically characterized by the deposit of misfolded proteins: the extracellular accumulation of beta amyloid peptide (Aβ), and the formation of intracellular neurofibrillary tangles. However, it is clear that many other cellular dysfunctions occur. Among these, a prominent role is exerted by the inflammatory process which is a consequence of the over-activation of glial cells. Indeed, several models of AD have demonstrated that glia modify their functions, losing the physiological supportive role. These cells instead acquire a pro-inflammatory phenotype, thus contributing to exacerbate Aβ toxicity. The relationship between neurodegeneration and neuroinflammation is strictly interdependent, and research efforts are now addressed to antagonize both processes simultaneously. Along this line palmitoylethanolamide (PEA) has attracted much attention because of its numerous pharmacological properties, particularly those related to the modulation of peripheral inflammation through the peroxisome proliferator activated receptor-α involvement. In light of these considerations, we explored the antiinflammatory and neuroprotective effects of PEA in rat neuronal cultures and organotypic hippocampal slices challenged with Aβ, and treated with PEA in the presence or absence of a selective peroxisome proliferator activated receptor-α antagonist. The data indicate that PEA is able to blunt Aβ-induced astrocyte activation and to exert a marked protective effect on neurons. These findings highlight new pharmacological properties of PEA and suggest that this compound may provide an effective strategy for AD.
Keywords: neurons